1991
DOI: 10.1093/oxfordjournals.humrep.a137472
|View full text |Cite
|
Sign up to set email alerts
|

Use of aniline blue to assess chromatin condensation in morphologically normal spermatozoa in normal and infertile men*

Abstract: Chromatin condensation is vital for the function of the spermatozoon as the motile carrier of the paternal genome. The degree of condensation can be shown with the aid of acidic aniline blue staining, which is able to discriminate between lysine-rich histones and arginine- and cysteine-rich protamines. Using this technique and employing the Düsseldorf classification of sperm morphology in cases of disturbance of spermatogenesis, it was demonstrated that chromatin condensation is impaired not only in malformed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
6

Year Published

1993
1993
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 0 publications
4
52
0
6
Order By: Relevance
“…Similarly, the peak intensity of the 785 cm À1 band varies between 0.45 and 0.74, indicating a var- (Figure 3g), but a few cells have peak ratios that are closer to that of the abnormal cells. This observation is consistent with previous dye binding studies of human sperm considered to have a normal head shape morphology [16]. This finding is extremely important.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similarly, the peak intensity of the 785 cm À1 band varies between 0.45 and 0.74, indicating a var- (Figure 3g), but a few cells have peak ratios that are closer to that of the abnormal cells. This observation is consistent with previous dye binding studies of human sperm considered to have a normal head shape morphology [16]. This finding is extremely important.…”
Section: Discussionsupporting
confidence: 93%
“…Currently clinicians selecting sperm for ICSI and other assisted fertilization methods using single sperm cells pick the sperm to be introduced into the eggs based primarily on their morphology, and in some cases a combination of morphology and motility. The Raman results, as well as the dye binding studies reported earlier [16], indicate that the population of sperm with normal head shapes is clearly heterogeneous in composition, and they may also be variable in their functionality. In summary, we have provided Raman-spectroscopic evidence obtained from analyses of individual cells that indicates that DNA packaging in human sperm cells with abnormal shape is different than in sperm with normal shape.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The potential value of adding these techniques to standard infertility evaluations lies in their ability to identify abnormal chromatin condensation in morphologically normal and abnormal spermatozoa (Dadoune et al, 1988;Hofmann and Hilscher, 1991). Aniline blue selectively stains lysine-rich histones (Terquem and Dadoune, 1983) and has been used as a clinical assessment of sperm chromatin condensation and associated infertility (Auger et al, 1990).…”
Section: Assessment Of Sperm Chromatin Structure In Fertility Evaluatmentioning
confidence: 99%
“…However, this effect was comparable in all current settings, when corrected for neutrally charged sperm. Multiple studies have reported an association between sperm chromatin compaction and abnormal sperm head morphology [61][62][63] and acrosome abnormalities [64]. Although the compaction of the nuclear chromatin and DNA integrity are two interdependent parameters [65,66], some studies have reported an association between them [67,68].…”
Section: Discussionmentioning
confidence: 99%